2006
DOI: 10.1111/j.1464-410x.2006.06124.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials in patients with biochemically relapsed prostate cancer

Abstract: In this section there is a wide diversity of mini‐reviews, covering several areas of interest for readers. Authors from the USA write about clinical trials in patients with biochemically relapsed prostate cancer, again bridging the divide between medical oncologists and urologists who specialise in urological oncological surgery. The second paper is a joint one from Germany and the USA, bringing the reader up to date with advances in the treatment of stress urinary incontinence. Finally there are two papers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…However, the modulation of PSA kinetics by treatment has not yet been shown to correlate with a clinical benefit for the patient. Nevertheless, in a recent review, a change in PSA‐DT was suggested as a clinical endpoint in trials for BCR 70. Different clinical endpoints and even different remission criteria make the comparison of study outcomes in PC difficult.…”
Section: Methodsmentioning
confidence: 99%
“…However, the modulation of PSA kinetics by treatment has not yet been shown to correlate with a clinical benefit for the patient. Nevertheless, in a recent review, a change in PSA‐DT was suggested as a clinical endpoint in trials for BCR 70. Different clinical endpoints and even different remission criteria make the comparison of study outcomes in PC difficult.…”
Section: Methodsmentioning
confidence: 99%
“…Sin embargo, la modulación de la cinética del PSA con tratamiento sistémico no ha mostrado todavía correlación con un beneficio clínico para el paciente. No obstante, en una revisión reciente, se ha sugerido el cambio del PSA-DT como criterio de evaluación en ensayos clínicos de recidiva bioquímica 47 . En general, las diferencias en los criterios de valoración clínica e incluso de los criterios de remisión hacen que sean difíciles las comparaciones de los resultados de los estudios en cáncer de próstata.…”
Section: Elección De Los Criterios Clínicos De Evaluaciónunclassified